2011
DOI: 10.1103/physrevlett.107.126804
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Airy Beam Generated by In-Plane Diffraction

Abstract: We report an experimental realization of a plasmonic Airy beam, which is generated thoroughly on a silver surface. With a carefully designed nanoarray structure, such Airy beams come into being from an in-plane propagating surface plasmon polariton wave, exhibiting nonspreading, self-bending, and self-healing properties. Besides, a new phase-tuning method based on nonperfectly matched diffraction processes is proposed to generate and modulate the beam almost at will. This unique plasmonic Airy beam as well as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
193
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(203 citation statements)
references
References 27 publications
5
193
1
1
Order By: Relevance
“…Potential applications of our results to recent experiments employing AiBs [11] are also outlined. They include optical manipulation of small particles [12], generation of curved plasma channels in air [13,14], and generation of surface plasmons with parabolic trajectories [15][16][17][18], to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…Potential applications of our results to recent experiments employing AiBs [11] are also outlined. They include optical manipulation of small particles [12], generation of curved plasma channels in air [13,14], and generation of surface plasmons with parabolic trajectories [15][16][17][18], to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Direct generation of the Airy beam from laser cavity could be realized by imprinting an aperiodic binary grating on the output coupling mirror. 15 The Airy modes also exist in the form of non-diffracting surface plasmon, [16][17][18] self-accelerating acoustics, 19 electron beams, 20 as well as spatiotemporal non-spreading light bullets. 21 In the present work, an ultra-long needle focus was experimentally generated through the creation of a rectangularly symmetric Airy beam (SAB) 22,23 with binary spectral amplitude modulation.…”
Section: Introductionmentioning
confidence: 99%
“…These studies also proposed that these waves could be used in different ways in optical micromanipulation [15], plasma guidance [16,17], and routing surface plasmon polaritons [18][19][20]. It was also found that, like Airy beams, Bessel waves have the same feature [18][19][20][21]. Due to the force of gravity, Airy beams move in their path along parabolic * Correspondence: fvcelebi@ybu.edu.tr trajectories.…”
Section: Introductionmentioning
confidence: 99%